2012
DOI: 10.2478/s13382-012-0061-3
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of inner ear potassium recycling genes as potential factors associated with tinnitus

Abstract: Tinnitus is defined as a perception of sound in the absence of an external acoustic stimulus. Several factors are known to influence tinnitus, e.g. hearing loss, noise exposure, age, and hypertension. As only certain individuals develop tinnitus in the presence of the above risks and in approximately 50% of cases tinnitus is not attributed to any particular cause, the question arose whether this inter-individual susceptibility to tinnitus could be explained by the influence of genetic factors. Objectives: To t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 30 publications
0
29
0
1
Order By: Relevance
“…Tinnitus candidate gene selection has included genes enriched in cardiovascular function ( ACE, ADD1 ), neurotrophic factors ( BDNF, GDNF ), ion recycling pathways ( KCNE1, KCNE3, SLC12A2 ), GABA B receptor subunit ( KCTD12 ), and serotonin receptor/transporter ( HTR1A, SLC6A4 ) function. Presently, nine case-control studies have examined a combined total of 18 genes that are summarized in Table 2 (Kleinjung et al, 2006; Deniz et al, 2010; Sand et al, 2010, 2011, 2012a,b; Pawełczyk et al, 2012; Orenay-Boyacioglu et al, 2016; Yüce et al, 2016). For brevity, we describe selected case-control association studies with potentially significant results.…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Tinnitus candidate gene selection has included genes enriched in cardiovascular function ( ACE, ADD1 ), neurotrophic factors ( BDNF, GDNF ), ion recycling pathways ( KCNE1, KCNE3, SLC12A2 ), GABA B receptor subunit ( KCTD12 ), and serotonin receptor/transporter ( HTR1A, SLC6A4 ) function. Presently, nine case-control studies have examined a combined total of 18 genes that are summarized in Table 2 (Kleinjung et al, 2006; Deniz et al, 2010; Sand et al, 2010, 2011, 2012a,b; Pawełczyk et al, 2012; Orenay-Boyacioglu et al, 2016; Yüce et al, 2016). For brevity, we describe selected case-control association studies with potentially significant results.…”
Section: Complex Genetics Approachesmentioning
confidence: 99%
“…PCR-RFLP: polymerase chain reaction-restriction fragment length polymorphism; VNTR: variable number tandem repeat The study from Pawełczyk et al also included the analysis of eight further genes involved in the potassium recycling pathway (GJB1, GJB2, GJB3, GJB4, GJB6, KCNJ10, KCNQ1, KCNQ4) but results were not significant (Pawełczyk et al, 2012) .…”
Section: Introductionmentioning
confidence: 99%
“…In another study, authors investigated the effect of acute and chronic salicylate treatment on the expression of NR2B, Arg3.1, and Egr-1 in an animal model of tinnitus, and they found both mRNA levels and the protein expression of NR2B and Arg3.1 increased in rats that were chronically administered salicylate [33] . In a study conducted with inner ear potassium recycling genes, significant associations were observed for two variants in KCNE1 and one SLC12A2 gene [34] . Furthermore, Sand et al [35] reported that GDNF genotypes together with BDNF genotypes predict tinnitus severity in women but not in men.…”
Section: Discussionmentioning
confidence: 99%
“…Este tipo de estudio sólo permite identificar variantes ligadas a un gen concreto y requieren estudios a escala genómica previa para proponer genes candidatos. Por otra parte, la selección de variantes puede presentar un sesgo de selección, por la asociación entre el marcador genético en estudio y la variante genética de riesgo verdadera (desequilibrio de ligamiento), resultando difícil determinar cuál es la variante que confiere el riesgo para la fenotipo (21) Hasta ahora se han realizado 9 estudios de casos-control con 18 genes candidatos (10)(11)(12)(13)(22)(23)(24)(25)(26). (Tabla 1).…”
Section: Genética De Los Acúfenosunclassified